Investigation of lubricating and dynamic performances for high-speed spur gear based on tribo-dynamic theory - Ouyang, Tiancheng; Huang, Guicong; Chen, Jingxian; Gao, Binxu; Chen, Nan (Tribology international, 2019)
Lubrication and vibration are crucial to the reliability and efficiency of gear device, especially in high-speed, heavy-load condition. In this study, a novel model based on tribo-dynamic theory is introduced to investigate the lubricating and dynamic performances of high-speed spur gear. In conjunction with a finite element model, the time-varying meshing stiffness and static transmission error are derived precisely in the form of Fourier series. An efficient iterative algorithm, integrated Newmark method with multigrid method, is developed for solving the governing equations. The simulation results indicate that it is necessary to utilize tribo-dynamic model to assist lubrication design and vibration control of spur gear in high-speed condition. •A new tribo-dynamic model combined a six degrees of freedom lump parameter model with a thermal mixed EHL model is proposed to study the lubricating and dynamic performances for high-speed spur gear.•In conjunction with a finite element model, the time-varying meshing stiffness and static transmission error are derived precisely in the form of Fourier series.•The effect of input torque on the asperity load ratio, film temperature rise and dynamic transmission error has been study.•The specific ratio λr is defined to reveal the relationship between film thickness, asperity load ratio and surface roughness.